Molecular characterization and antimicrobial resistance profiles of Salmonella typhimurium isolated between 1995 and 2002 from organs and environments of diseased poultry in South Africa - Van Heerden, Henriette (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.